2019
DOI: 10.1055/s-0039-1692683
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Failed Microvascular Decompression in Patients with Trigeminal Neuralgia

Abstract: Background Microvascular decompression (MVD) has been widely accepted as a definitive therapy for primary trigeminal neuralgia (TN). However, some patients may not experience relief of TN symptoms following surgery. In this study, the findings of redo MVD are discussed. Methods Between 2015 and 2017, 205 patients with primary TN underwent MVD surgery in Shanghai Tongren Hospital. Among these patients, 187 had immediate complete relief of symptoms, 8 improved apparently, and 10 reported no symptom r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Offending vessel could be perforator that encircle the nerve, which is one of the common causes of difficult MVD and result in incomplete decompression. 13 Huang et al 14 and Cho et al 15 reported high rate of incomplete decompression in failed MVD and proposed that it was one of the main causes of the surgical failure providing support for the need of repeat MVD. Lee et al classified the possible causes of MVD failure into three categories, offending vessel omission, insufficient decompression and untouched NVC site.…”
Section: Discussionmentioning
confidence: 99%
“…Offending vessel could be perforator that encircle the nerve, which is one of the common causes of difficult MVD and result in incomplete decompression. 13 Huang et al 14 and Cho et al 15 reported high rate of incomplete decompression in failed MVD and proposed that it was one of the main causes of the surgical failure providing support for the need of repeat MVD. Lee et al classified the possible causes of MVD failure into three categories, offending vessel omission, insufficient decompression and untouched NVC site.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] Sufficient decompression of TN and thorough exploration of both sensory and motor roots during MVD is a prerequisite to obtaining optimal pain relief in adult patients with PTN. 31 The main purpose of this study is derived from this clinical fact that it is still unclear why a sizable portion of adult PTN patients with explicit NVC are unable to obtain satisfactory shortand long-term CPR even after sufficient decompression of TN during MVD. According to reports, MVD has a recurrence rate of about 10%, which is significantly lower than that of traditional pharmacotherapy and other neurosurgical interventions, with non-arterial compression being one of the contributing factors.…”
mentioning
confidence: 99%